Enhancing School Canteen Practices: A Catalyst for Healthier and Ethical Student Snacking - Puspita Handayani; Galuh Ramana Hanum; Supriyadi Supriyadi; Muhammad Bagas Mahaputra; Ario Khairul Habib (Indonesian Journal of Cultural and Community Development, 2023)
The prevalence of substandard and non-halal school snacks is a pressing concern, as 35% of school snacks reportedly contain addictive substances, contributing to potential health risks among students [1]. Instances of elementary school children falling ill due to consumption of mobile vendor snacks have surged [2]. Prompted by these issues, our dedicated team embarked on an intervention to educate and revamp school canteen practices under the framework of BERSERIH (Clean, Healthy, Beautiful, and Halal). Focusing on Madrasah Ibtidaiyah Muhammadiyah 3 in Penatarsewu village, our selected canteen represented a nutritional fulcrum for students. The pre-intervention state depicted an inadequately healthy, clean, and appealing canteen, compounded by a lack of food variety, thus enticing students to seek alternative, risk-laden snack sources. Through imparting knowledge on healthy, halal food and revitalizing canteen aesthetics, a noticeable surge in canteen snack purchases by students was observed, alongside heightened food diversity facilitated by canteen vendors. This initiative underscores the pivotal role of canteens in fostering nutritious and ethical snacking habits among school children. Highlight: Prevalence of Unhealthy Snacks: The study addresses the alarming presence of substandard and addictive-laden school snacks, with 35% containing harmful substances, posing potential health risks to students. Mobile Vendor Snacks and Health Implications: Instances of elementary school children falling ill after consuming snacks from mobile vendors highlight the urgent need for improved school canteen practices to ensure students' well-being. Educational Intervention and Canteen Transformation: The research outlines the successful implementation of the BERSERIH framework to educate and transform school canteen practices, resulting in increased consumption of healthy, halal snacks and a diverse food selection among students. Keyword: School Snacks, Health Risks, Canteen Practices, Halal Food, Student Well-being